2015
DOI: 10.1101/gad.268128.115
|View full text |Cite
|
Sign up to set email alerts
|

WSB1 promotes tumor metastasis by inducing pVHL degradation

Abstract: The von Hippel-Lindau tumor suppressor pVHL is an E3 ligase that targets hypoxia-inducible factors (HIFs). Mutation of VHL results in HIF up-regulation and contributes to processes related to tumor progression such as invasion, metastasis, and angiogenesis. However, very little is known with regard to post-transcriptional regulation of pVHL. Here we show that WD repeat and SOCS box-containing protein 1 (WSB1) is a negative regulator of pVHL through WSB1's E3 ligase activity. Mechanistically, WSB1 promotes pVHL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
68
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(70 citation statements)
references
References 63 publications
2
68
0
Order By: Relevance
“…MiRNAs regulate many cellular functions such as cell proliferation, differentiation, and migration, and are implicated in pathologic conditions including cancer [13, 14]. MicroRNA-145 (miR-145) is a tumor suppressor that inhibits tumor cell growth and metastasis in many cancers [15-18]. Interestingly, a number of recent studies have shown that miR-145 directly downregulates SMAD3 by binding to its three prime untranslated region (3'-UTR) [19-22].…”
Section: Introductionmentioning
confidence: 99%
“…MiRNAs regulate many cellular functions such as cell proliferation, differentiation, and migration, and are implicated in pathologic conditions including cancer [13, 14]. MicroRNA-145 (miR-145) is a tumor suppressor that inhibits tumor cell growth and metastasis in many cancers [15-18]. Interestingly, a number of recent studies have shown that miR-145 directly downregulates SMAD3 by binding to its three prime untranslated region (3'-UTR) [19-22].…”
Section: Introductionmentioning
confidence: 99%
“…These findings open new areas of research aimed at understanding how epigenetic changes at prometastatic loci are altered during tumor progression. Recent studies have also indicated that VHL activity in tumors can be regulated by WSB1, an E3 ligase that targets pVHL for ubiquitination and proteasomal degradation ( 27 ). WSB1 expression in tumor cells leads to HIF stabilization under normoxic and hypoxic conditions and correlates with metastasis in cancer patients (Fig.…”
Section: Hypoxic Signalingmentioning
confidence: 99%
“…WSB1 expression in tumor cells leads to HIF stabilization under normoxic and hypoxic conditions and correlates with metastasis in cancer patients (Fig. 1) ( 27 ).…”
Section: Hypoxic Signalingmentioning
confidence: 99%
“…Given that WSB1 increases one of the most important glycolytic proteins-HIF-1α and contributes to human malignancy [10], thus WSB1 was predicted as a potentially functional target gene of miR-592. As shown in Figure 3A, one predicted binding site in the WSB1 3′-UTR with a perfect complementarity to the seed region of the miR-592 was identified.…”
Section: Resultsmentioning
confidence: 99%
“…More recent evidence suggested that WSB1 is a direct target of HIF-1α in a human HCC model [9]. Interestingly, WSB1 can in turn stabilize HIF-1α by protecting it from VHL-induced degradation [10]. Thus it is possible that WSB1 may promote HCC progression through altering cancer cell metabolism.…”
Section: Introductionmentioning
confidence: 99%